Keggin-type polyoxometalate-based supramolecular complex for selective oxidation of styrene to benzaldehyde. Issue 17 (17th September 2020) - Cui, Wen-Jing; Zhao, Qing; Zhu, Hao-Tian; Hu, Na; Ma, Yuan-Yuan; Han, Zhan-Gang; Li, Yang-Guang
Abstract: A Keggin-type polyoxometalate (POM)-based supramolecular complex with the formula of [Co(H2 O)3 ]2 (ttb)2 [HBW12 O40 ]·2H2 O (1 ) (ttb = 1, 3, 5-tri(1, 2, 4-triazol-1-ylmethyl)-2, 4, 6-trimethylbenzene) was synthesized via hydrothermal method and characterized by single-crystal X-ray diffraction, IR and powder X-ray diffraction analyses. In 1, [Co(H2 O)3 ] 2+ cations are connected with the adjacent ttb ligands to form a porous two-dimensional (2-D) cationic layered network, and the [HBW12 O40 ] 4− polyoxoanions are encapsulated between the layers through intermolecular interactions, generating a POM-capsulated 3-D supramolecular network. Integrating the advantage of Co 2+ with [HBW12 O40 ] 4−, 1 as a heterogeneous catalyst displays a synergistically improved catalytic performance for oxidation of styrene. It can achieve almost 98% conversion of styrene in 4 h with about 99% selectivity of benzaldehyde product, which is about five times more than the catalytic activities of the single components (Co(OAc)2 ·4H2 O or K5 BW12 O40 ). A series of comparative analyses showed that the high catalytic performance of 1 is mainly attributed to the synergistic effect of unsaturated metal sites and polyoxoanions. This work provides an approach for developing highly efficient POM-based heterogeneous catalysts toward the selective oxidation of styrene. Graphical Abstract: